Quality of Root Canal Obturation Performed by Senior Undergraduate Dental Students - Moradi, Saeed; Gharechahi, Maryam (Iranian Endodontic Journal, 2013)
Introduction: There is a direct relationship between the quality of root canal obturation and success of endodontic therapy. The aim of the present study was to assess the quality of canal obturation performed by undergraduate dental students at the Faculty of Dentistry, Mashhad University of Medical Sciences, Mashhad, Iran. Materials and Methods: Records of 200 endodontically treated teeth from patients who were visited by undergraduate students between 2009 and 2010, at the Endodontic department, Faculty of Dentistry, Mashhad University of Medical Sciences, were randomly selected for evaluation. Periapical radiographs of all treated teeth were assessed in terms of canal obturation quality (i.e. adequate density and length). Statistical analysis of data was carried out using SPSS software and chi-square test. The Statistical significance level was set at P=0.05. Results: Forty-five percent of teeth fulfilled the criteria of an acceptable root canal obturation. Adequate length and density of root filling was found in 89% and 34% of teeth, respectively. There was a significant difference between maxillary and mandibular teeth regarding the length of root canal obturation (P=0.004). A significant difference was observed between molars and other tooth types. The frequency of root canals with an acceptable filling was significantly greater in the anterior teeth compared to premolars or molars. Conclusion: The technical quality of root canal treatment performed by undergraduate dental students was found to be less than ideal.